Effects of Oxygen-fuel Ratio on Structure and Property of Detonation Gun Sprayed WC Coating - ZHAO Li-ying; LIU Ping-an (Cailiao gongcheng, 2016)
The tungsten carbide coating with both high hardness and dense microstructure was prepared by optimizing the detonation gun spraying parameters. The phase identifications and microstructure of the coating were observed and analyzed by optical microscope, X-ray diffraction (XRD) and energy dispersive spectrometer (EDS). The results show that with the increase of oxygen-fuel ratio, the hardness and adhesive strength of the coating firstly enhance and then decrease, while porosities firstly decrease and then increase. When the oxygen fuel ratio is too low, slow particle flight speed and insufficient melt are the main reasons for the degradation of the coating compactness and mechanical properties. When the oxygen fuel ratio is too high, particle decarburization and binder phase nonuniform contract in the cooling process are the determining factors to the coating structure and properties. When the oxygen-fuel ratio is 1.15, comprehensive performance of the coating is optimal, and the oxidation and decarburization of the coating can be effectively reduced. The Vickers microhardness HV0.3 of cross-section reaches 1178kg·mm-2, the porosity is 0.86%, and the bonding strength between the coating and substrate is 152MPa.